Considerations for a sustainability framework for neglected tropical diseases programming. (28th January 2021) - Espinal, Marcos; Kruk, Margaret E; Mohamed, Madame Cisse Mariama; Wainwright, Emily
Abstract: Addressing neglected tropical diseases (NTDs) is critical to achieving universal healthcare and the Sustainable Development Goals. Significant strides are being made to expand NTD programs, but these programs still need to be fully incorporated into national governance, financing, planning and service delivery structures. The World Health Organization has developed a sustainability framework that calls for governments to create a vision and a multisector plan to achieving sustainability. Several critical factors need to be considered to avoid undermining progress toward disease elimination and control targets, while merging program components into national systems.